INTRODUCTION AND COMPARATIVE CHARACTERISTIC OF MALUS SIEVERSII VARIETY CLONES OF THE DZHUNGARIAN POPULATION (Experimental biology, 2021)
Malus sieversii is a mountain-steppe and valley tree species widespread in the mountains of southeast Kazakhstan. The aim of this work is to study the structure of variability and intraspecific differentiation of Malus sieversii (Ledeb.) M. Roem. based on a complex of morphological features of generative organs and the characteristics of the seasonal rhythm of apple trees in natural and introduction conditions. Malus sieversii is a mountain-steppe and valley tree species widespread in the mountains of southeast Kazakhstan. The introduction collection of Malus sieversii’s forms growing in the Main Botanical Garden of Almaty (GBS) is a source of global genetic resources. According to the research data, the intraspecific variability of the studied apple tree forms was characterized by heterogeneous morphometric parameters of the generative organs. The studied apple trees are distinguished by heterogeneous morphometric parameters. Large-flowered forms were observed both in natural populations and in GBS. In the conditions of the Dzungarian Alatau, the large sizes of flowers were characteristic of the forms in the gorges of Pikhtovaya and Mushabay. Among the variety clones the sample TP-19 selected in the Pikhtovaya distinguished itself by the large size of the corollas.